Characterization of dhaincha accessions based on morphological descriptors and biomass production (Journal of the Bangladesh Agricultural University, 2016)
Forty five accessions of dhaincha germplasms were collected from different parts of Bangladesh and characterized on the basis of morphological descriptors and biomass production ability. Thirty eight accessions were identified as Sesbania bispinosa, four as S. cannabina and two as unidentified Sesbania spp. One accession as S. rostrata was included for comparison. Both at seedling and maturity stages, wide and significant differences were observed among the accessions of different dhaincha germplasms for their biomass production capability and other morphological descriptors. At the seedling stage, total dry mass (TDM) production varied from 10.2 to 41.6g 30-plants1. At the maturity stage, plant height, total number of branches and base diameter of dhaincha germplasms varied from 347.5474.7cm, 10.423.7, and 1.94.9cm, respectively. The highest amount (4.10kg 10-plants1) of above-ground TDM was produced in one accession of unidentified Sesbania sp. followed by S. rostrata and one accession of S. cannabina (3.85kg 10-plants1), and the lowest TDM (0.9kg 10-plants1) was measured in two accessions of S. bispinosa. It may be concluded that the biomass production capability of at least two accessions of local Sesbania germplasms were higher/comparable to that of exotic S. rostrata. It will be too early to make a conclusive remark based on only a few dhaincha germplasms. A detailed study with a large number of germplasms collected from whole Bangladesh is obviously needed to reach in a precise conclusion.J. Bangladesh Agril. Univ. 13(1): 55-60, June 2015